2020
DOI: 10.1039/d0ra00505c
|View full text |Cite
|
Sign up to set email alerts
|

Cesium polytungstates with blue-tint-tunable near-infrared absorption

Abstract: Revisiting Wöhler's method (1824), Cs-doped tungsten bronzes were synthesized by reducing Cs-polytungstate at high temperature, and were pulverized into nanoparticles for determining their optical properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(29 citation statements)
references
References 39 publications
(70 reference statements)
2
27
0
Order By: Relevance
“…12 The corresponding NIR absorption of pulverized nanoparticles increased gradually with reduction. 12 The XPS profiles of W−4f for the CPT samples are reproduced in Figure 2a, with deconvoluted components of W 7/2 5+ , W 7/2 6+ , W 5/2 5+ , and W 5/2 6+ . In the present study, W 4+ was not observed, and neither was it reported in previous studies of HTBs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…12 The corresponding NIR absorption of pulverized nanoparticles increased gradually with reduction. 12 The XPS profiles of W−4f for the CPT samples are reproduced in Figure 2a, with deconvoluted components of W 7/2 5+ , W 7/2 6+ , W 5/2 5+ , and W 5/2 6+ . In the present study, W 4+ was not observed, and neither was it reported in previous studies of HTBs.…”
Section: Resultsmentioning
confidence: 99%
“…Besides evaporating out most of the hydrogenic components, this hightemperature reduction gradually transformed Cs 4 W 11 O 35 to Cs 0.32 WO 3−y according to X-ray diffraction (XRD). 12 In this paper, we shall call the intermediate state of the two-phase mixture "Cs polytungstate" (CPT). In addition to reducing the Cs 4 W 11 O 35 crystal at high temperature (the "A" process), we obtained Cs-HTB via direct crystallization and reduction of the raw materials at intermediate temperatures (the "B" process).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The films based on CWO nanoparticles whose optical properties are absorptive can shield more than 80% of NIR light while maintaining high visible light transmittance. 34 The pure PDLA film exhibits high transmittance (Z75%) in the Vis-NIR region (400-2500 nm). Compared with PDLA, the prepared composite film has higher transmittance in visible light, but stronger shielding performance in NIR (800-2000 nm).…”
Section: Resultsmentioning
confidence: 99%